LytF, a Novel Competence-Regulated Murein Hydrolase in the Genus Streptococcus - Berg, Kari Helene (American Society for Microbiology, 2012)
Streptococcus pneumoniae and probably most other members of the genus Streptococcus are competent for natural genetic transformation. During the competent state, S. pneumoniae produces a murein hydrolase, CbpD, that kills and lyses noncompetent pneumococci and closely related species. Previous studies have shown that CbpD is essential for efficient transfer of genomic DNA from noncompetent to competent cells in vitro. Consequently, it has been proposed that CbpD together with the cognate immunity protein ComM constitutes a DNA acquisition mechanism that enables competent pneumococci to capture homologous DNA from closely related streptococci sharing the same habitat. Although genes encoding CbpD homologs or CbpD-related proteins are present in many different streptococcal species, the genomes of a number of streptococci do not encode CbpD-type proteins. In the present study we show that the genomes of nearly all species lacking CbpD encode an unrelated competence-regulated murein hydrolase termed LytF. Using Streptococcus gordonii as a model system, we obtained evidence indicating that LytF is a functional analogue of CbpD. In sum, our results show that a murein hydrolase gene is part of the competence regulon of most or all streptococcal species, demonstrating that these muralytic enzymes constitute an essential part of the streptococcal natural transformation system.